The Importance of Website Usability in Digital Marketing A Review (International Journal of Innovative Research in Computer Science & Technology, 2023)
The effectiveness of any digital marketing  strategy is strongly dependent on the user experience of the  website being promoted. A website that is difficult to  browse, confusing or slow to load the content can result in  a poor user experience and, as a result there is a loss in  leads or consumers. A website that is easy to use, well organized and optimised for mobile devices, on the other  hand can help improve user engagement, raise conversion  rates and ultimately boost the success of digital marketing  initiatives. This paper shows the significance of website  usability in digital marketing and explores the impact of  website usability on user experience and how it can affect  the key performance indicators such as bounce rates,  session duration and conversion rates. By emphasising the  importance of website usability in digital marketing, this  paper intends to give actionable insights for business  looking to improve the user’s website’s user experience  and maximise the digital marketing campaigns.  Understanding the impact of website usability on the  performance of digital marketing efforts allows  organisations to make informed decisions regarding  website design and functionality to create good user  experience that increases engagement and conversion.
Keywords: digital Marketing; mobile optimisation (responsiveness); search functionality (SEO); website design; website usability